THE PROBLEM OFSIMULATION AND EDUCATION (In J.Baudrillard creative field) - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the philosophical analysis of the simulation problem in the educational process from Jean Baudrillard point of vew is made.